KUALITAS KINERJA TENAGA MEDIS DI RUMAH SAKIT SITTI MARYAM KOTA MANADO - AHMAD, FITRIA; Rumapea, Patar; Mambo, Rully (Sam Ratulangi University, 2017)
Based on the result observation at the Sitti Maryam Hospital Manado city still has some problems such asconcerning the quality performance of medical personnel as service providers to the community. Assessment of theperformance of qualified medical personnel by providing good service views of the reliability, responsiveness,assurance, emphaty, and tangibles. For the purpose of this study is to know the performance quality of medicalpersonnel at the Sitti Maryam Hospital Manado city. The research use descriptive qualitative research. Informantresearch as much as 8 (eight) informant that is, one leadership of hospital, two doctors, one person nurse, one personstaff employees hospital, and three patients. Data collection techniques use are observation techniques, interviewtechniques, and documentation techniques, as well as data analysis techniques that are use are data reduction, datapresentation, and conclusion drawing. Based on result of research through observations, data collection andinterview process that the researcher did, then research on the quality performance of medical personnel in the SittiMaryam Hospital not good enough, in view of the indicators of reliability, responsiveness, assurance, empathy andtangibles. For reliability is still not good, because the services provided are not time there are still some medicalpersonnel who performed the task has not been maximum. And also the lack of surgeons that resulted in patientshaving to wait for health services. For the responsiveness is still not good, because the parient complains against theprovision of service that are not on time is not good responded. For the assurance is good, because welfare thepatient treated at Sitti Maryam Hospital is guaranteed. For emphaty is not good because there are still some nursesand employees Sitti Maryam Hospital is less good to speak to the patient. And for the tangibles is not good, becausefor general facilities such as chairs in each ward is still lacking in meeting the needs of patiens.Keyword: Quality, Performance Of Medical Personnel